Skip to main content
Factor
Tick mark Image
Evaluate
Tick mark Image

Similar Problems from Web Search

Share

3\left(2a^{2}+3a\right)
Factor out 3.
a\left(2a+3\right)
Consider 2a^{2}+3a. Factor out a.
3a\left(2a+3\right)
Rewrite the complete factored expression.
6a^{2}+9a=0
Quadratic polynomial can be factored using the transformation ax^{2}+bx+c=a\left(x-x_{1}\right)\left(x-x_{2}\right), where x_{1} and x_{2} are the solutions of the quadratic equation ax^{2}+bx+c=0.
a=\frac{-9±\sqrt{9^{2}}}{2\times 6}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
a=\frac{-9±9}{2\times 6}
Take the square root of 9^{2}.
a=\frac{-9±9}{12}
Multiply 2 times 6.
a=\frac{0}{12}
Now solve the equation a=\frac{-9±9}{12} when ± is plus. Add -9 to 9.
a=0
Divide 0 by 12.
a=-\frac{18}{12}
Now solve the equation a=\frac{-9±9}{12} when ± is minus. Subtract 9 from -9.
a=-\frac{3}{2}
Reduce the fraction \frac{-18}{12} to lowest terms by extracting and canceling out 6.
6a^{2}+9a=6a\left(a-\left(-\frac{3}{2}\right)\right)
Factor the original expression using ax^{2}+bx+c=a\left(x-x_{1}\right)\left(x-x_{2}\right). Substitute 0 for x_{1} and -\frac{3}{2} for x_{2}.
6a^{2}+9a=6a\left(a+\frac{3}{2}\right)
Simplify all the expressions of the form p-\left(-q\right) to p+q.
6a^{2}+9a=6a\times \frac{2a+3}{2}
Add \frac{3}{2} to a by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
6a^{2}+9a=3a\left(2a+3\right)
Cancel out 2, the greatest common factor in 6 and 2.